United Against AIDS - The Story of TASO - Strategies for Hope (MGS Video (Kampala), 2007)
This film, along with a book of the same name, was produced to mark the 20th anniversary of the establishment, in November 1987, of The AIDS Support Organisation (TASO) in Uganda. TASO has since grown into one of the largest and most widely respected NGOs in Africa. It provides treatment, care, counselling and social support to over 80,000 clients and their families. All TASO services are provided free of charge, including antiretroviral therapy (ART). Peter Ssebbanja, the author of the book, was one of the original founding members of TASO and still works for the organisation. Noerine Kaleeba, TASO’s founder and first director, speaks on the film about the ‘family spirit’ which has inspired TASO staff and volunteers to maintain high standards while expanding rapidly. In both the book and the film, TASO clients describe how the organisation has empowered them to ‘live positively with HIV’ - a term coined by TASO twenty years ago, which has since resonated throughout the world. Produced by MGS Video (Kampala) for the Strategies for Hope Trust.
Free